TCP throughput enhancement over wireless mesh networks. - Li-Ping Tung (IEEE Communications magazine)
TCP is the predominant technology used on the Internet to support upper layer applications with reliable data transfer and congestion control services. Furthermore, it is expected that traditional TCP applications (e.g., Internet access) will continue to constitute the major traffic component during the initial deployment of wireless mesh networks. However, TCP is known for its poor throughput performance in wireless multihop transmission environments. For this article, we conducted simulations to examine the impact of two channel interference problems, the hidden terminal and exposed terminal, on TCP transmissions over wireless mesh networks. We also propose a multichannel assignment algorithm for constructing a wireless mesh network that satisfies the spatial channel reuse property and eliminates the hidden terminal problem. The simulation results demonstrate the effectiveness of the proposed approach in improving the performance of TCP in wireless multihop networks.